Channel, robot, ghost, intruder, chameleon or mediator? Various roles of the cabin interpreter - Tymoszuk, Katarzyna Barbara (Glottodidactica, 2019)
The following paper is aimed at presenting and discussing the various roles – often mutually conflicting, or even unwanted – of the cabin interpreter. The starting point for the presented examples is an outline of the debate between practitioners and theoreticians of translation, centred around the actions that are expected from or prohibited for an interpreter in the situation of linguistic and cultural interpretation. The discussed concepts of roles are subsequently confronted with real-life examples of translator behaviours which have been taken from a broad research corpus obtained by the author